Why do firms co-operate for innovation? A comparison of Austrian and Finnish CIS 3 results - Bernhard Dachs; Bernd Ebersberger; Andreas Pyka (Universität Augsburg, Institut für Volkswirtschaftslehre, 2004)
This paper analyzes co-operative behavior of innovative firms in Finland and Austria. We use data from the third wave of the Community Innovation Survey (CIS 3). Descriptive statistics indicate that the rate of innovators is quite similar in Austria and Finland, while the number of cooperating enterprises is considerably higher in Finland. Econometric analysis reveals that a number of factors that determine co-operative arrangements are only significant in the one or the other country. We conclude that co-operative behavior in the two countries is much more dependent on national factors and much deeper rooted in the underlying innovation systems than the existing literature may assume.
urn:nbn:de:bvb:384-opus4-712026
Keywords: L24; O31; 330; co-operation; CIS 3; Austria; Finland; Innovation; Unternehmenskooperation; Vergleich; Innovationspolitik; Österreich; Finnland